Fresnoite glass-ceramics – A review. (October 2018) - Wisniewski, Wolfgang; Thieme, Katrin; Rüssel, Christian
Abstract: The crystallization of fresnoite from glasses enables to produce a wide variety of materials including piezoelectric glass-ceramics due to the aligned growth of these crystals in the amorphous matrix. The crystal structure of fresnoite leads to interesting pyroelectric, piezoelectric and non-linear optical properties and is one of the few known non-ferroelectrics which can be easily produced as polycrystalline but polar materials. This review provides a summary of the properties of fresnoite crystals as well glass-ceramics containing fresnoite crystals. A special focus is the preparation of oriented and polar glass-ceramics and the resulting properties. The literature concerning the complete process from the amorphous glass to crystal nucleation and the subsequent growth is reviewed.